High peak viraemia followed by spontaneous HIV‐1 control in women living with HIV‐1 subtype A1 in East Africa - Yifan Li; Bethany L. Dearlove; Eric Lewitus; Hongjun Bai; Shida Shangguan; Phuc Pham; Meera Bose; Eric Sanders‐Buell; Shana Howell Miller; Yvonne Rosario; Philip K. Ehrenberg; Sodsai Tovanabutra; et al. (Journal of the International AIDS Society)
Abstract Introduction Cases of spontaneous control of HIV‐1 can help define strategies to induce remission. Since the identification of viral control in the absence of treatment typically occurs after a prolonged period post‐HIV‐1 diagnosis, our knowledge of the early events after HIV‐1 acquisition that led to viral control is limited. Methods The RV217 prospective cohort enrolled 2276 participants in East Africa (Kenya, Uganda, Tanzania) and Thailand between 2009 and 2015. We analysed HIV‐1 sequences and clinical data from 102 individuals who were diagnosed with acute HIV‐1 infection and had a negative HIV‐1 RNA test in the week before. We focused on 69 participants with longitudinal follow‐up and identified viraemic controllers who maintained viral loads <2000 copies/ml for over a year without treatment. We evaluated viral genetic and clinical features that are associated with viral control. Results Eleven women from East Africa showed control of viral replication for an average duration of 891 (range: 405–1425) days within an average of 130 days from diagnosis. The majority were living with subtype A1 (n = 6), or A1 recombinant strains (n = 4), with one living with subtype D; 10 were from Kenya, one from Uganda. Controllers had significantly slower CD4+ T cell decline (p = 0.028) and higher Natural Killer (NK) cell counts (p = 0.047) than non‐controllers, but none carried human leukocyte antigen (HLA) alleles previously reported to be associated with viral control. Peak viraemia was recorded at an average of 541 million copies/ml with no difference between controllers and non‐controllers (p = 0.97). Viral loads became lower in controllers (3459 copies/ml) than in non‐controllers (23,157 copies/ml) as early as nadir viraemia (p = 0.009), with a more significant difference observed at set point (1069 vs. 24,084 copies/ml, respectively; p<0.0001). Conclusions Our findings confirm the role of HIV‐1 subtype A1 in mediating viral control. The fact that controllers showed high viral loads in acute infection indicates that these viruses were not intrinsically impaired for replication, underlining the intersection between host immunity and favourable genotypes in the subsequent control of HIV‐1. These data suggest that conducting HIV‐1 remission studies in East Africa could provide favourable conditions to achieve durable post‐treatment control of viraemia.